Deuteron NMR investigation on orientational order parameter in polymer dispersed liquid crystal elastomers. Issue 40 (13th October 2020) - Rešetič, Andraž; Milavec, Jerneja; Domenici, Valentina; Zupančič, Blaž; Bubnov, Alexej; Zalar, Boštjan
Abstract : Orientational order parameter of magnetically aligned liquid crystal elastomer particles suspended in a cured silicone matrix is assessed using 2 H-NMR spectroscopy. Obtained results correspond well with the composite's thermomechanical response. Abstract : Polymer-dispersed liquid crystal elastomers have been recently introduced as a thermomechanically active composite material, consisting of magnetically oriented liquid crystal elastomer particles incorporated in a cured polymer matrix. Their thermomechanical properties are largely governed by the degree of imprinted particle alignment, which can be assessed by means of deuterium perturbed 2 H-NMR. Spectra of samples with various degrees of imprinted particle alignment were recorded and the results simulated using the discrete reorientational exchange model developed for determining the dispersion of liquid crystal elastomer's domain orientational distribution. We show that the model can be applied to measure the orientational distribution of embedded liquid crystal microparticles and successfully determine the orientational order parameter in the composite system. Thermomechanical measurements correlate well with the obtained results, thus additionally confirming the validity of the applied method.